An Investigation on Bio-aerosol Concentrations in the Different Wards of Hospitals of Isfahan University of Medical Sciences - Heshmatollah Nourmoradi; Mahnaz Nikaeen; Mohammad Mehdi Amin; Maryam Hatamzadeh (مجله دانشکده پزشکی اصفهان, 2011)
Background: Bioaerosol is defined as airborne particles such as living organisms include bacteria, viruses, fungi and their related metabolites, such as endotoxin. The exposure to bioaerosols in the hospital may causes infection especially in immunocompromised patients. The purpose of this study was to investigate the Bioaerosol concentrations in air of various parts of three hospitals of Isfahan University of medical sciences, Iran. Methods: An Anderson biosampler was used for the bacterial and fungal collection. The effect of factors such as humidity, temperature and outdoor Bioaerosol concentrations were also evaluated. Findings: The lowest mean of fungal and bacterial concentration was observed in hospital operating rooms and the highest concentration was detected in infectious diseases ward of hospital 1 and 2 and surgery ward of hospital 3. Significantly, bacterial levels were found to be higher in hospital wards than outdoor; except hospital operating roo. Conclusion: Our results show that bioaerosol concentrations in hospitals were relatively high and in particular, the higher levels of bacteria than outdoor might be related to the presence of patients, their activity, unsuitable ventilation and disinfection. Therefore, environmental control measures are needed to assure hospital environmental quality especially in wards with immunocompromised patients.